Caenorhabditis elegans in the biological activity research of tea: From “little transparent” to “big star” - Lingwei Yang; Zhonghua Liu; Ligui Xiong; Yushun Gong (Journal of Functional Foods)
Caenorhabditis elegans (C. elegans) has proven to be a valuable model organism for assessing active ingredients. The wide array of active compounds found in tea, including tea polyphenols, amino acids, alkaloids, and aromatic substances, has provided numerous health benefits. In C. elegans, active ingredients such as catechins and their derivatives, L-theanine, and caffeine have exhibited various biological effects, including slowing down aging, enhancing environmental adaptations, regulating protein homeostasis and glycolipid metabolism, and participating in immunomodulation. The worms play a crucial role in studying the mechanisms of tea polyphenols and exploring the bioactivity of catechin derivatives. Here, we discuss how these active ingredients promote worms' health, and elucidate their mechanisms of action. We further offer recommendations for utilizing nematodes and microorganisms as host-microbe models to combine multiple active tea components in the diet or to investigate the unique chemical components present in other teas, aiming to enhance our understanding of the health benefits of tea consumption on biological organisms.